Sequential Measurements of Pentraxin 3 Serum Levels in Patients with Ventilator-Associated Pneumonia: A Nested Case-Control Study - BİLGİLİ, BELİZ; HAKLAR, GONCAGÜL; BİLGİN, HÜSEYİN; CİNEL, İSMAİL HAKKI; DURMUŞOĞLU, LÜTFİYE; ARSLANTAŞ, MUSTAFA KEMAL; AY, NADİYE PINAR (HINDAWI LTD, 2018)
Purpose. The main purpose of this study was to investigate the dynamics of pentraxin 3 (PTX3) compared with procalcitonin (PCT) and C-reactive protein (CRP) in patients with suspicion of ventilator-associated pneumonia (VAP). Materials and Methods. We designed a nested case-control study. This study was performed in the Surgical Intensive Care Unit of a tertiary care academic university and teaching hospital. Ninety-one adults who were mechanically ventilated for >48 hours were enrolled in the study. VAP diagnosis was established among 28 patients following the 2005 ATS/IDSA guidelines. Results. The median PTX3 plasma level was 2.66 ng/mL in VAP adults compared to 0.25 ng/mL in non-VAP adults (p < 0.05). Procalcitonin and CRP levels did not significantly differ. Pentraxin 3, with a 2.56 ng/mL breakpoint, had 85% sensitivity, 86% specificity, 75% positive predictive value, and 92.9% negative predictive value for VAP diagnosis (AUC = 0.78). Conclusions. With the suspicion of VAP, a pentraxin 3 plasma breakpoint of 2.56 ng/mL could contribute to the decision of whether to start antibiotics.
Keywords: C-REACTIVE PROTEIN; ATTRIBUTABLE MORTALITY; PROCALCITONIN; DIAGNOSIS; MARKER; PTX3